A taxonomia revisada de Bloom como instrumento de análise do material digital de matemática do estado de São Paulo - Leite, Damiele de Assis [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This final course project aims to identify the relationship between the skills and exercises offered in each lesson of the Digital Material (DM) of the state of São Paulo for the first semester of 2024, according to its objectives, classifying and leveling them according to Bloom's Revised Taxonomy, thus identifying whether there is cohesion between the purpose of the exercises and the skills that will be acquired in the lesson. This is qualitative and documentary research that seeks to collect existing data on the subject, aiming to compare and relate them to the absorption of concepts learned in the classroom through Bloom's Revised Taxonomy. The study concludes that the DM is aligned with the objectives of the lessons, but prioritizes activities that reach the lowest levels of Bloom's Revised Taxonomy, failing to achieve the competencies indicated by the Common Core Curriculum (BNCC), which are reinforced by the São Paulo Curriculum. It is suggested that the material be improved with proposals that encourage analysis, creation, and application of knowledge in real-life situations within interdisciplinary contexts, so that the skills required by the BNCC can be acquired.

Este trabalho de conclusão de curso tem como objetivo identificar a relação entre as habilidades e os exercícios oferecidos em cada aula do Material Digital (MD) do estado de São Paulo do primeiro bimestre do ano de 2024 de acordo com os objetivos dela, classificando-as e nivelando-as de acordo com a Taxonomia Revisada de Bloom, identificando assim se existe coesão entre a finalidade dos exercícios com as habilidades que serão adquiridas na aula. Trata-se de uma pesquisa qualitativa, do tipo documental, que busca coletar dados já existentes sobre o tema, visando compará-los e relacioná-los com a absorção dos conceitos aprendidos em sala de aula por meio da Taxonomia Revisada de Bloom. O estudo conclui que o MD está alinhado aos objetivos das aulas, porém privilegia atividades que alcançam os níveis mais baixos da Taxonomia Revisada de Bloom, não conseguindo atingir as competências indicadas pela Base Comum Curricular (BNCC) que são reforçadas pelo Currículo Paulista. Sugere-se aprimorar o material com propostas que estimulem análise, criação e aplicação do conhecimento em situações reais em contextos interdisciplinares para que habilidades pedidas na BNCC sejam obtidas.
Bloom's revised taxonomy as an instrument for analyzing digital mathematical material from the state of São Paulo
Keywords: Funções matemáticas; Funções elementares; Educação matemática; Taxonomia revisada de Bloom; Ensino-aprendizagem; Mathematical functions; Elementary functions; Mathematics education; Revision of Bloom’s taxonomy and teaching-learning